2015
DOI: 10.1007/s00268-015-2985-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Bile Duct Tumor Thrombus: Surgical Outcomes and the Prognostic Impact of Concomitant Major Vascular Invasion

Abstract: Concomitant MVI was a strong prognostic factor in the setting of HCC with BDTT. Extended hepatectomy provided a good prognosis for the patients with BDTT alone without MVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…Kasai et al have reported previously that major vascular invasion is a negative prognostic indicator for HCC patients with BDTT. 18 These results suggest that BDTT alone does not affect prognosis and only does so in conjunction with other prognostic factors, such as vascular invasion, poor differentiation, or large size.…”
Section: -8 Yeh Et Al Reported the Relationship Between The Pathogenmentioning
confidence: 69%
See 1 more Smart Citation
“…Kasai et al have reported previously that major vascular invasion is a negative prognostic indicator for HCC patients with BDTT. 18 These results suggest that BDTT alone does not affect prognosis and only does so in conjunction with other prognostic factors, such as vascular invasion, poor differentiation, or large size.…”
Section: -8 Yeh Et Al Reported the Relationship Between The Pathogenmentioning
confidence: 69%
“…7 However, according to several reports, routine bile duct resection is not recommended unless direct invasion of the BDTT into the bile duct is suspected. 8,12,18 Shiomi et al reported that the survival of their bile duct-preserved group was similar to that of their bile duct-resected group. 19 Recently, Yamamoto et al reported using bile duct-preserving surgery for HCC with BDTT-called the "peeling off technique"…”
Section: -8 Yeh Et Al Reported the Relationship Between The Pathogenmentioning
confidence: 99%
“…Surprisingly, our study found 12.5% lymph node metastasis in HCC with HBDTT, which is higher than those reported in previous literatures. Some studies had mentioned higher incidence of lymphovascular invasion in HCC with BDTT than HCC without BDTT [41,42]. This finding is unexpected and may suggest that HCC with HBDTT is more aggressive via lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 88%
“…Cholangitis and hemobilia, which often develop in association with bile duct invasion, are also immediate threats to survival. In addition, HCC involvement of the bile duct could theoretically be accompanied by portal vein thrombosis, which is one of the worst prognostic factors for HCC patients [12]. …”
Section: Introductionmentioning
confidence: 99%